Repair and rehabilitation of concrete structures using confinement: A review. (15th February 2017) - Ma, Chau-Khun; Apandi, Nazirah Mohd; Sofrie, Chin Siew Yung; Ng, Jen Hau; Lo, Wen Haur; Awang, Abdullah Zawawi; Omar, Wahid
Highlights: Research findings on design and applications of repair techniques using confinement are discussed. FRP confinement has significant potential in repairing applications. The lacking in the current research development is discussed. Issues that hindered the widespread use of confinement are critically analysed. Abstract: Repair and rehabilitation of existing damaged concrete structures have emerged as one of the most important construction activities globally. Money used on repairing damaged structures has exceeded that of the money used on building new structures. The earthquake strikes recently in Asian countries such as Japan and Borneo Malaysia have attracted the attention of structural engineers and scholars on the research and development of rapid repairing techniques. Confinement is one of the rapid repairing techniques that is popular and proven to be efficient in restoring the original capacities of damaged concrete. Although many research investigations have been done to confirm the suitability of these techniques in repairing damaged concrete structures, there are several barriers that hindered the widespread use in practical. These barriers include the lack of design and installation guidelines and long-term durability studies. This paper reviewed the use of confinement as a repairing technique and the design and installation processes involved in order to facilitate the research development in this field. The findings have reached a consensus that confinement repair techniques are effective as they can restore the original capacities of damaged concrete members. More investigations are still required to establish sufficient design guidelines and lastly, the confinement pressure loss over a service period should be tested to ensure the durability of the repaired concrete members.